ANALISIS SIKAP DAN PERILAKU MASYARAKAT TERHADAP HUTAN PENELITIAN PARUNG PANJANG - Surati Surati (Pusat Penelitian dan Pengembangan Sosial, Ekonomi, Kebijakan dan Perubahan Iklim, 2014)
Community's participation in forest management has potential to reduce forest disturbances. Attitudes and behavior of local communities towards the forest need to be understood and formulated, and then used in reformulating the management strategy of forest research. The study was carried out at Parung Panjang Research Forest (PPRF), aimed to find out the correlation between internal and external characteristics, and community's attitudes and behavior about research forest in their surrounding area, and the way to realize participatory management of PPRF. Internal and external characteristics data were analyzed using the distribution of mean frequency value while community attitudes and behavior were analyzed by Likert scale method. Results showed that the level of income and interaction with the forest have significant relationship with the attitudes and behavior of forest communities. Attitudes and behavior towards Parung Panjang Reseacrh Forest is positive, meaning that the community supports the existence and forest management. Socioeconomic conditions of forest communities is low, and therefore, the realization of participatory forest management research is expected to improve their welfare without damaging the forest.